Clinical Outcomes in Adolescents and Adults After the Fontan Procedure - Dennis, Mark; Zannino, Diana; du Plessis, Karin; Bullock, Andrew; Disney, Patrick J.S.; Radford, Dorothy J.; Hornung, Tim; Grigg, Leeanne; Cordina, Rachael; d’Udekem, Yves; Celermajer, David S. (Journal of the American College of Cardiology, 2018)
Long-term outcomes of Fontan patients who survive to age ≥16 years have not been well characterized. The Australian and New Zealand Fontan Registry (ANZFR) provides a unique opportunity to understand survival and complication rates in Fontan patients who transition to adult congenital heart disease centers. This study sought to describe the survival and complications of adult patients who have had a Fontan procedure. The study analyzed outcomes in patients ≥16 years of age who were prospectively enrolled in the ANZFR. Data from all 683 adult survivors from the ANZFR were analyzed. Mortality status was confirmed from the National Death Index. There were 201 atriopulmonary (AP) connections and 482 total cavopulmonary connections (249 lateral tunnels and 233 extracardiac conduits). For these subjects, the survival rate at age 30 years was 90% (95% CI: 87% to 93%), and it was 80% (95% CI: 75% to 87%) at 40 years of age. Survival at age 30 years was significantly worse for the patients with AP connections (p = 0.03). At latest follow-up, only 53% of patients were in New York Heart Association functional class I. After the age of 16 years, 136 (20%) had experienced at least 1 new arrhythmia, 42 (6%) required a permanent pacemaker, 45 (7%) had a thromboembolic event, and 135 (21%) required a surgical reintervention. Only 41% (95% CI: 33% to 51%) of Fontan patients were free of serious adverse events at 40 years of age. This comprehensively followed cohort showed that a variety of morbid complications is common in Fontan adults, and that there is a substantial incidence of premature death, particularly in patients with AP connections. [Display omitted]